Detection of EBV, CMV and HSV-1 in subgingival samples of HIV positive and negative patients with chronic periodontitis. - Laura Escalona; Dayahindara Veitía; María Correnti (Universidad de Concepción., 2016)
Objective: To detect the presence of infection by EBV (Epstein-Barr Virus), CMV (Cytomegalovirus) and HSV-1 (Herpes Simplex Virus type 1) in subgingival samples from HIV- positive patients under HAART (High Activity Antiretroviral Therapy), HIV- positive patients without HAART, HIV-negative patients with chronic periodontitis and healthy controls. Methodology: Crevicular fluid samples of 11 HIV+ patients on therapy were evaluated, 6 without antiretroviral therapy, 7 HIV- negative subjects with chronic periodontitis and 7 periodontally-healthy controls. PI (Plaque index), GI (Gingival Index), PD (probing depth) and CAL (Clinical Attachment Loss) were registered at six sites per each tooth in all teeth and subgingival plaque samples of a tooth were collected per quadrant. Nested PCR was used to detect EBV and endpoint PCR to detect infection by CMV and HSV-1. Results: Clinical parameters showed statistically significant differences between HIV-positive patients and subjects with chronic periodontitis compared with the control group (p<0.05). DNA of EBV was detected mainly in HIV-positive patients under HAART, 91% (10/11). DNA of CMV was detected mainly in patients without HAART, 67% (4/6), while HSV-1 was observed in 27% (3/11) of patients under HAART. In the control group no virus was detected. Coinfection was observed in 50% of HIV patients without HAART, 36% of HIV patients with HAART and 14% of HIV-negative with chronic periodontitis. Conclusion: Viral infection was prevalent in HIV patients under HAART and EBV was the primary viral infection detected in HIV-positive patients with chronic periodontitis.